The influence of organisational strategy, recruitment strategy and organisational culture on succession planning in South Africa’s Department of International Relations and Cooperation - Ramaboea, Stella Julie (Vaal University of Technology, 2017)
In terms of the Public Service Act, 1994, as amended by Act 30 of 2007, all government departments operate under a recruitment system whereby applicants and employees are selected for positions based on their qualifications for the job. Equity and fairness are underlying democratic values and principles of the system. Therefore, the system guards against pre-determined successors until such time as all qualified candidates are provided an equal opportunity to apply for, and be considered, for the job (RSA 1994). However, organisations need to ensure that the appropriate people are in place with the required values, skills and competencies that are necessary to bring about change and accomplish goals to drive organisational strategy forward. It is also necessary to ensure that a suitable leadership team is chosen to help preserve and build upon an organisation’s existing vision, mission and values. Ensuring that leaders have the appropriate skills, abilities and competencies is crucial to assist an organisation to implement its strategic direction and overall goals and objectives. The purpose of this study was to investigate the influence of organisational strategy, recruitment strategy and organisational culture on effective succession planning in the Department of International Relations and Cooperation (DIRCO). In this study, focus was on trait behavioural, situational and chaos leadership and management theories; and their relationship to succession planning. The study made use of a quantitative research technique. Quantitative primary research was conducted by employing a self-administered questionnaire in the gathering of primary data for the study. The target population comprised employees (from entry level to executive levels) of DIRCO based in Gauteng Province as well as 127 South African Embassies and Consulates in foreign countries. Descriptive analysis was used in the analysis of the sample composition and participants’ perception of succession planning at DIRCO. Furthermore, confirmatory factor analysis and structural equation modelling (SEM) was used to assess model fit and to test the hypotheses. The results of the study confirmed that the recruitment strategy of DIRCO does not create opportunities for identification of internal talent. In order to address these deficiencies, it is recommended that DIRCO identify, mentor and promote diverse pools of internal candidates through succession planning. A proper succession plan will provide an organisation with a surplus of talent and will assist officials to realise their potential. DIRCO prefers to recruit external candidates rather than developing training programmes that will prepare the internal workforce for future leadership positions. The results indicate that lack of organisational and recruitment strategies have substantial influence on organisational processes.
M. Tech. (Department of Business Administration, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Organisational strategy; Leadership theories; Recruitment strategy; Organisational culture; Succession planning; Strategic planning -- South Africa.; Personnel management -- South Africa.; Corporate culture -- South Africa.; Executive succession -- Planning -- South Africa.; South Africa -- Department of International Relations and Cooperation.; Dissertations, Academic -- South Africa.